The Effects of the Nirvana Fitness Exercise Programme on Perceived Stress and Cognition - Rima Solianik; Jelena Ivanova (Lithuanian Sports University, 2022)
Background. Mind and body exercise programmes, such as Tai Chi, Yoga and Pilates, can be successfully applied for stress reduction and cognitive function enhancement, however Nirvana Fitness training effects on perceived stress and cognition remain equivocal. The aim. To determine the effects of Nirvana Fitness training on perceived stress and cognition. Methods. The study included 20 women. They were randomly assigned to a control (n=10) or experimental (n=10) group. Participants in the experimental group participated in the Nirvana Fitness exercise programme, which consisted of a 50-minute class twice a week for 8 weeks. Participants in the control group were asked to maintain their daily routines. Changes in perceived stress and cognitive performance were evaluated. Results. The Nirvana Fitness exercise programme significantly decreased (p<0.05) perceived stress and improved (p<0.05) inhibitory control and cognitive flexibility, whereas spatial and working memory remained unchanged. Conclusion. The Nirvana Fitness programme can be used as an effective method to decrease stress and improve attention in women. Keywords: memory, attention, women, mind and body exercise programmes